Behavioural Finance Factors and Investors Decision in Cross River State - Dr. Nkamare Stephen Ekpo; Inok Edim Edim; Emefiele Charles Chike; Ebong Iniobong Ephraim; Odama Patrick Ojeka; Ekeng Ekpenyong Nsa (Law and Economy, 2025)
The study empirically examined tests of behavioral finance factors and investors decision. The specific objectives were to: examine the relationship between overconfidence and investment decision, ascertain the relationship between herding and investment decision, and to investigate the relationship between Risk perception and investment decision. This study employed a survey research design in order to reproducing an extensive and exact picture of the stock market of Nigeria behavioral financing/ investment decisions. The target population of this study included all individual investors in the stock market in the year 2023, with the population of one hundred and ninety-six (196). Primary data was employed, and data were analyzed using Pearson product moment correlation. Based on the results, the major findings of the study included were: there was a significant relationship between overconfidence and investment decision, there was a significant relationship between herding and investment decision and finally, there was a significant relationship between Risk perception and investment decision. The study concluded that behavioral finance factors measured with overconfidence, Herding and Risk Perception have significant relationship on the decision of individual investors. It is recommended that behavioral financial factors should be considered which could have an impact on investor’s decision.